Effectiveness of School-Based Nutrition Education Interventions on Nutrition Knowledge Outcomes: A Systematic Review and Meta-Analysis - Canneysha Lathiefa Zahra; Fatimah Nur Fadillah; Trias Mahmudiono (Universitas Airlangga, 2026)
Background: The Double Burden of Malnutrition (DBM) remains a major global public health problem, particularly in low- and middle-income countries. Children and adolescents increasingly experience undernutrition (such as stunting and micronutrient deficiencies) and are overweight or obese. Poor diets, low nutritional knowledge, and high consumption of ultra-processed foods contribute to this problem. Schools are strategic settings for intervention; however, evidence on the effectiveness of school-based nutrition education remain limited. Objectives: Evaluating the impact of school-based nutrition education interventions on nutrition knowledge among children and adolescents. Method: A systematic review and meta-analysis were conducted using studies from PubMed and Scopus. Eligible studies included randomized controlled trial or pre-post intervention in school-aged children (9–17 years). Standardized mean differences (SMD) were used to estimate pooled effect. Results: Of the 1,253 studies identified, three studies met the inclusion criteria, with participants from Ghana and Malaysia. Two studies reported an increase in nutrition knowledge, while one study showed no effect. Meta-analysis showed a small but statistically significant increase in the intervention group compared to control group (SMD=0.15; 95% CI: 0.05–0.26; p=0.005), with high heterogeneity (I²=78%). Conclusion: School-based nutrition education interventions have small but significant effects on improving nutrition knowledge in children and adolescents. However, variation across studies and limited evidence suggest the need for more rigorous and comprehensive intervention to assess long-term impact on eating behavior and nutritional status.